MEMBANGUN SENSE OF COHERENCE ANAK DIFABEL: PERSPEKTIF TEOLOGI IMAGO DEI BERDASARKAN KEJADIAN 1:26-27 - Zinzendorf R A Dachi (Manna Rafflesia, 2026)
Children with disabilities have difficulty actualizing themselves in independence and interacting with their peers. Life experiences involving emotions such as self-actualization, understanding the meaning of life and readiness to interact with physical, mental, and intellectual disabilities often cause children to become easily angered and emotionally unstable. Negative reactions from the environment and discriminatory treatment make children with disabilities tend to withdraw, leading to a negative self-concept, feeling stupid, strange, and useless. According to Aaron Anthonovsky's solutogenesis theory, this can be restored if children with disabilities have a strong sense of coherence. This study aims to find out how to build a sense of coherence in children with disabilities from a theological perspective. A descriptive qualitative method with a literature study approach was carried out to examine aspects of the sense of coherence and theological principles from the teaching of humans as the image and likeness of God in Genesis 1:26-27. The findings obtained that the aspects of understanding, manageability, and meaningfulness which are components of the sense of coherence can be strengthened through teaching humans as the image and likeness of God to build a sense of coherence in children with disabilities. The novelty of this research lies in the reconceptualization of the identity of children with disabilities from merely being objects of service to becoming subjects who have a strong sense of coherence based on the theological understanding of imago Dei.